2022
DOI: 10.1021/acscatal.2c00613
|View full text |Cite
|
Sign up to set email alerts
|

A Redox-Switchable Gold(I) Complex for the Hydroamination of Acetylenes: A Convenient Way for Studying Ligand-Derived Electronic Effects

Abstract: A gold complex with a naphthalene-di-imide-functionalized N-heterocyclic carbene (NHC) ligand was prepared and characterized. The electrochemical studies reveal that the complex is able to undergo two successive reduction events, associated to the reduction of the NDI moiety of the NHC ligand. Once the redox-switchable properties of this Au­(I) complex were proven, the complex was tested in the hydroamination of terminal alkynes. The activity of the neutral complex was moderate-to-high for this reaction, but t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 54 publications
0
21
0
3
Order By: Relevance
“…2 a We recently described two NHC ligands fused to naphtalenediimide (NDI) and perylene-diimide (PDI) moieties that were coordinated to rhodium, iridium 5 and gold. 6 The presence of the NDI or PDI units appended to the NHC ligand allowed toggling between three levels of electronic control of the metal, and this was used for studying the redox-switchable catalytic properties of the complexes in the cycloisomerization of alkynoic acids, 5 a and in the hydroamination of alkynes. 6 In view of these previous results, we herein describe the preparation of a series of dimetallic rhodium and iridium complexes in which the two metals are bound by a NDI-di-propylene-di-imidazolylidene ligand.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 a We recently described two NHC ligands fused to naphtalenediimide (NDI) and perylene-diimide (PDI) moieties that were coordinated to rhodium, iridium 5 and gold. 6 The presence of the NDI or PDI units appended to the NHC ligand allowed toggling between three levels of electronic control of the metal, and this was used for studying the redox-switchable catalytic properties of the complexes in the cycloisomerization of alkynoic acids, 5 a and in the hydroamination of alkynes. 6 In view of these previous results, we herein describe the preparation of a series of dimetallic rhodium and iridium complexes in which the two metals are bound by a NDI-di-propylene-di-imidazolylidene ligand.…”
mentioning
confidence: 99%
“…6 The presence of the NDI or PDI units appended to the NHC ligand allowed toggling between three levels of electronic control of the metal, and this was used for studying the redox-switchable catalytic properties of the complexes in the cycloisomerization of alkynoic acids, 5 a and in the hydroamination of alkynes. 6 In view of these previous results, we herein describe the preparation of a series of dimetallic rhodium and iridium complexes in which the two metals are bound by a NDI-di-propylene-di-imidazolylidene ligand. Given that, apparently, the redox-active NDI unit is electronically disconnected from the two imidazolylidene groups due to the presence of the two n -propyl chains, it is expected that the modification of the oxidation state of the NDI core should impart little or negligible influence on the electron-donating ability of the two NHC units.…”
mentioning
confidence: 99%
“…1,2 Organometallic supramolecular assemblies obtained by metal-carbene-directed self-assembly from N-heterocyclic carbene (NHC) ligands have been dramatically developed in stimulus-responsive organometallic materials, catalysis, and photochemical reactions. [3][4][5][6][7][8] This strategy utilizes the directional advantages of metal-carbene bonding to adequately control the design of various NHC-based supramolecular architectures. In the library of reported NHC complexes, a series of macrocycles, cages and other interlocked organometallic complexes have been constructed from coinage metals (Ag I , Au I , and Cu I ) and well-designed NHC ligands, binding in a fixed linear geometry.…”
Section: Introductionmentioning
confidence: 99%
“…In two recent studies, we showed how the fusion of a naphthalene diimide (NDI) moiety on the backbone of an Nheterocyclic carbene provided a ligand with redox-switchable properties, which was used for the preparation of rhodium and iridium catalysts for the cycloisomerization of alkynoic acids, [13] and in the preparation of gold(I) complexes for the hydroamination of alkynes. [14] The functionalization of the NHC ligands with the NDI core, allowed three levels of electronic control of the catalyst, given that the ligand can operate either in its neutral form, or in the one-or two-electron reduced forms of the NDI moiety, thus constituting a rare example of multistate redox switchable catalysis. We think that the scarcity of multi-state switchable catalysts is rather surprising, [15] given that multi-state switchable molecules feature prominently in molecular machines [16] and molecular electronics.…”
Section: Introductionmentioning
confidence: 99%